A new proposal for an easy-to-calibrate DNI clear-sky model: a performance analysis and validation in different geographical locations - César D. Sánchez-Segura; Manuel I. Peña Cruz (Nova Scientia)
Clear sky models can be used as a reference for sizing solar technology applications and for solar irradiance forecasting purposes. Properly defining the parameters of each clear sky model implies knowing the altitude, latitude, longitude, as well as various climatic characteristics of the study site, which makes its implementation difficult. Derived from the above, in this work a new easy-calibration methodology was developed to obtain a functional clear sky model for any day of the year and any geographical location. By proposing calibration coefficients obtained from only a couple of DNI measurements, and without taking into account the geographical characteristics or climatic conditions of the study site, the developed clear sky model was tested in a global context using a period of 11 years (2010-2020) with databases of 71 solarimetric stations, obtaining an average RMSD that ranges between 6.48% (arid climate) to 7.97% (equatorial climate). In addition, the developed model was compared with a variety of clear sky models to determine the percentage of accuracy of these against clear and non-clear sky days, thus demonstrating that the accuracy of the proposed model can be superior in different scenarios.